1995
DOI: 10.4315/0362-028x-58.11.1275
|View full text |Cite
|
Sign up to set email alerts
|

Antimycotic and Antiaflatoxigenic Effect of Lactic Acid Bacteria: A Review

Abstract: Lactic acid bacteria are extensively used in the fermentation of a wide variety of food products and are known for their preservative and therapeutic effects. Many lactic acid bacteria species have been reported to inactivate bacterial pathogens, and numerous antibacterial substances have been isolated. However, the antimycotic and antimycotoxigenic potential of lactic acid bacteria has still not been fully investigated. Fermented foods such as cheese can be contaminated by molds and mycotoxins. Mold causes sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 0 publications
5
45
0
2
Order By: Relevance
“…An important observation in the present study was a decrease in ergosterol, aflatoxin and fumonisin contents on fermentation at 24 and 36 h, which could be attributed to the presence of high amounts of Lactobacillus after fermentation. This is in accordance with many investigations that have reported the control of mould growth and mycotoxin production in liquid cultures and grains by lactic acid bacteria (Laitila et al, 2002;Peltonen et al, 2001;ElNezami et al, 1998;Gourama and Bullerman, 1995;Karunaratne et al, 1990). Various traditional products from sorghum prepared by fermentation have shown reduction in mycotoxins through fermentation involving lactic acid bacteria (Adegoke et al, 1994;Zinedine et al, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…An important observation in the present study was a decrease in ergosterol, aflatoxin and fumonisin contents on fermentation at 24 and 36 h, which could be attributed to the presence of high amounts of Lactobacillus after fermentation. This is in accordance with many investigations that have reported the control of mould growth and mycotoxin production in liquid cultures and grains by lactic acid bacteria (Laitila et al, 2002;Peltonen et al, 2001;ElNezami et al, 1998;Gourama and Bullerman, 1995;Karunaratne et al, 1990). Various traditional products from sorghum prepared by fermentation have shown reduction in mycotoxins through fermentation involving lactic acid bacteria (Adegoke et al, 1994;Zinedine et al, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…Rabie and Marais 23 have suggested that sorghum malt has the highest fungal load of all South African foods and feeds. While sorghum malt microflora also include bacteria and yeasts, the mould contaminants have been of the greatest concern because of their potential mycotoxigenicity 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Foodborne and food grade LAB have been studied much more than Bacillus species or propionic bacteria and their antifungal activities have been reported by several authors throughout the years (20,21,22,23,24,25,26,27). Table 1 shows some of the publications that have demonstrated the antifungal activity of LAB, which vary from broad to very specific among and within species.…”
Section: Lactic Acid Bacteriamentioning
confidence: 99%